Bioética clínica na concepção de profissionais de saúde em um hospital de pequeno porte - Zimmerman, Alessandra Caroline Ortiz (2019)
Bioethics is a field of recent knowledge that seeks, through its different approaches, to produce reflections and practices permeated by respect for human dignity, as well as the planet and other living beings, concerned with survival as a whole through increasing advances of the technology and the mismatch between their creations and the knowledge to manage them. Clinical bioethics arises from the need to discuss ethical dilemmas arising from the practice between health professionals and patients in the context of health and illness, as well as life and death. In addition, Latin American bioethicists raise the need to think about the problems arising from the vulnerability of underdeveloped peoples by calling for a social ethic. Still, bioethics to safeguard people as an end, wants biomedical science and its applications to contemplate the autonomy of patients and their rights to their choices before their own lives. This study aims to understand how bioethics is being conceive and how this field can be found in a small-scale hospital setting. For that, nurses, doctors, nutritionists and psychologists, through individual semi-structured interviews, interviewed eight professionals. It is a clinical-qualitative study, guided by the epistemology of complexity, contemplating the interdisciplinary crossings existing in this study.